Connectivity infrastructure and Central Java’s economics performance - Karnoto, Suparjito Bin; Setiawan, Wawan; Fauzi, Hasan; Anggunani, Rizky; Rafikalif, Dinar (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
This research aims to describe the benefits of developing connectivity infrastructure on economic performance in the Central Java region. The data used in this research are road length, the wide of an area, economic growth, human development index and poverty rate per district/city in Central Java in 2023. By using a Cartesian diagram approach (4 quadrant analysis), a comparison is made between the ratio of road length and the wide of an area with economic growth, comparison between the ratio of road length and the wide of an area with the human development index (HDI) and the comparison between the ratio of road length and the wide of an area with the poverty level to obtain an overview of road infrastructure development and economic performance in Central Java. The research results show that road infrastructure development plays an important role in encouraging increased economic performance in the Central Java region.